PAWSing Student Stress: A Pilot Evaluation Study of the St. John Ambulance Therapy Dog Program on Three University Campuses in Canada - Dell, Colleen Anne; Chalmers, Darlene; Gillett, James; Rohr, Betty; Nickel, Chelsea; Campbell, Lori; Hanoski, Rita; Haguerud, Josh; Husband, Alicia; Stephenson, Coby; et al. (Canadian Journal of Counselling and Psychotherapy, 2015)
Student mental health is a concern on university campuses, and animal-assisted interventions are one response. This article presents the immediate and three-month follow-up outcomes of a pilot evaluation study of the St. John Ambulance Therapy Dog program at three Canadian universities. Analyzing a sample of 403 students and 16 handlers/observers at the events and 87 students at follow-up, we found that the therapy dogs offer love and support. Love is understood as having reciprocal love for the dogs and gaining positive feelings from visiting with them. Support is understood as destressing and relaxing by interacting with the dogs. Implications for mental health supports for university students are suggested.